﻿Programa Madrugada Viva : análise da formulação e implementação de política pública de redução da violência e acidentes no trânsito causados pelo uso indevido do álcool no Estado do Espírito Santo - Nascimento, Andréa dos Santos (2008)
The objective of this study is to analyze the processes of formulation and implementation of a policy for reduction of violence and mortality in car accidents, called Programa Madrugada Viva (Live Dawn Program), in the State of Espirito Santo. The study analyses the groups of interests involved in the formulation and implementation of the Program; the resistance and obstacles faced; the arguments used for the maintenance of the Program; and the role of the media in the process. In the analyses of the policies, we tried to create a dialogue, rebuilding the paths, grounding, and political criteria that are discussed, and which later enter the governmental agenda. With this objective, we discuss the concepts of Government and Civil Society highlighting the theory of the enhanced role of the state as in Gramsci, as well as the role of the media, and the way a theme enters a public agenda. We analyze how alcohol plus driving became a public- health problem in the national scenario of the 20th century. As a study of case, we chose to collect data from several sources. We interviewed the mentors of the Program (Madrugada Viva) and researched documents (official ones, and newspaper clips from 2003 to 2007). The analysis of the contents was used to analyze the qualitative data. The problem alcohol/driving appear in a local context of successive car accidents involving drunkdriving, and in the national context as a discussion about health. The media was an important element in the acceptance and maintenance of Madrugada Viva. As a governmental initiative, it has suffered, along these four years, successive processes of evaluation that gave place to other programs: Praia Viva (Live Beach) and Montanha Viva (Live Mountain). Programs to face the problems of drinking and driving are recent and they challenge everyone involved in the process of formulation and implementation of public policies that are able to fight the problem. In fact, it is not restricted to the individual behavior of each driver, but also expresses the omission of governments that give in to other groups of capitalist interests (like businessmen, advertisement agencies, liquor traders, and large beer companies) instead of promoting educational campaigns, the regulation of alcoholic beverage commerce, as well as the prevention of this irreversible damage.